Sequential ADP-stimulated light transmission and multiple electrode aggregometry in patients taking aspirin and clopidogrel after non ST-elevation myocardial infarction - Meen, Øystein; Brosstad, Frank; Liestøl, Knut; Kunszt, Gabor; Bendz, Bjørn; Wettergreen, Marianne; Schjelderup, Nina M.; Andreassen, Trine; Erikssen, Gunnar (Scandinavian journal of clinical and laboratory investigation, 2012)
Abstract Background. Fast platelet function tests can identify weak clopidogrel responders, but data on variability over time in clopidogrel responsiveness in several clinical settings are lacking. We wanted to explore long-term variability of multiple electrode aggregometry (MEA) measurements and the agreement between MEA and light transmission aggregometry (LTA) in patients with non-ST elevation myocardial infarction (NSTEMI) treated with aspirin and clopidogrel. Methods. Parallel MEA and LTA were performed at baseline and after 6 and 12 weeks in 31 patients treated with percutaneous coronary intervention after NSTEMI. Adenosine diphosphate (ADP) concentrations 2 μM, 6.5 μM and 10 μM were used. Parallel testings in both arterial and venous blood were performed at baseline. MEA and LTA cut-off levels were applied to discriminate aggregation values suggesting presence or absence of high platelet reactivity (HPR). Results. Arterial and venous MEA and LTA aggregation were similar. Within-subject variability in both MEA and LTA aggregation throughout the study was moderate. According to MEA, eight patients had HPR at baseline (MEA aggregation > 47 U). Defining > 47% as the LTA aggregation HPR cut-off level, the same number of patients (eight) had HPR according to LTA. Of the 93 MEA/LTA observations 81 (87.1%) gave the same HPR classification. MEA vs. LTA agreement at baseline was slightly inferior to that obtained after 12 weeks. Conclusions. MEA and LTA aggregation in arterial and venous blood seem similar. Within-subject variability over time was moderate, and the agreement between LTA and MEA was good, and stable in most patients.